Discourse on Legal Aid for Children in Rape Crime Cases (Study of Decision Number 138/Pid.Sus/2020/PN.Pti) (Universitas Negeri Semarang, 2022)
Along with the times, it has implications for the development of a crime. Rape is one of the taboo criminal acts in society, if in the past rape was generally carried out by adults in this era, it is possible that children can become perpetrators and become victims of rape. Children are the image of the nation in the future who carry noble values ​​and ideals of the nation. The need for massive and sustainable legal and non-juridical protection of children is the obligation of all parties. The crime of rape committed by children against children is a special case where the handling is certainly not the same as handling other cases in general. Seeing further that the perpetrators and victims are still minors, there will be many conflicts between the sociological rules and the juridical aspects in general, the role of institutions and law enforcement officers is needed for the creation of justice. In solving the problem of rape committed by children with child victims, then there are two interests and two rights of children that are confronted with each other, both of which still have a long future ahead so that in handling it must receive special attention, even though this cannot be immediately eliminate the crime that has been committed by the child. Ordinary people will think that rape is a taboo subject, because of this mindset, the victim will tend to be cornered and just remain silent without getting justice. Victims of sexual violence/rape have the right to obtain legal assistance and obtain justice for the rights of victims who have been violated. Then how important is legal aid for victims of child rape crimes committed by children.